Devo, não nego, mas tenho um dinheirinho guardado: motivações para as pessoas manterem dívidas e investirem dinheiro ao mesmo tempo - Melo, Juliana Ranciaro de (2020)
To date, most studies on the role of debt in the consumer society have focused on studying debt in conjunction with the use of credit cards or loans. Thus, the main objective of this study was to identify the motivations that lead people to have debts and to save money at the same time. The specific objectives of the research were: i) to identify whether financial knowledge is related to the way people deal with debts and investments; ii) identify whether the behavior is different in view of the different types of expenses; iii) identify whether individuals understand the expenses that generate debt as necessary or superfluous. For this, an exploratory qualitative research, of an interpretative character, with in-depth interviews was carried out. 10 interviews were conducted that served as the basis for this study. The interviews took place between April and December 2019, with individuals chosen from a non-probabilistic sample by “snowball”. It was possible to identify that financial knowledge is not related to the possibility of having a financial life considered healthier and that individuals are unable to classify expenditures as necessary or superfluous. From the perspective of behavioral finance, most of the interviewees showed an absence of self-control and frequent absence. These results were analyzed in the light of theories of indebtedness, economic psychology, temporal orientation, materialism and compulsive or impulsive consumption. The market implications mainly concern the promotion of financial education in the country and in companies, even if these are already in the financial market, dynamics more focused on the conscious consumption of products such as credit cards, loans and overdraft and the use of interpersonal stimuli to address issues related to economics, finance and investments.